Adverse events associated with patient isolation: a systematic literature review and meta-analysis. (January 2022) - Saliba, R.; Karam-Sarkis, D.; Zahar, J-R.; Glélé, L.S.A.
Summary: Background: Patient isolation is widely recommended and used in healthcare institutions to prevent transmission of multidrug-resistant organisms (MDROs). However, its risk: benefit ratio is debated. Aim: To assess, based on newly published studies, whether or not there are physical and psychological adverse events associated with patient isolation. Methods: Systematic literature review and meta-analysis were performed in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Studies were systematically searched from PubMed, from May 1 st, 2009 to January 31 st, 2020. The concepts of the research questions were defined as: 'Adverse events', 'patient isolation or cohorting', and 'multi-drug resistant organisms colonized or infection patients'. Three reviewers independently screened studies and extracted data. All statistical analysis was performed with Stata Software and R. Findings: After screening titles of 15, 921 articles and abstracts of 196, and reviewing full texts of 50 studies, 19 studies were included. Studies were divided into three groups: four qualitative studies, seven observational studies suitable for meta-analysis, and eight other observational studies. Meta-analysis shows no adverse events related to clinical care or patients' experience associated with patient isolation. Conclusion: More studies with correct methodology, including a control group and standardized inclusion criteria, must be conducted to confirm our results.